Designing a Chatbot Application Using the Flask Framework and Rule-Based Algorithm - Haeruddin, Haeruddin; Sabariman, Sabariman; Su, Vincent (Jurnal Teknologi Dan Sistem Informasi Bisnis, 2025)
This research aims to develop a website based chatbot application implemented at PT. International Hardware Indo using the Flask framework and Rule-Based algorithm. The application is designed to improve customer service efficiency by providing quick answers to frequently asked questions, reducing the workload of customer service, and addressing operational time constraints. The chatbot development process follows the Waterfall methodology, which includes requirements analysis, design, implementation, testing, and maintenance. The Rule-Based algorithm is employed to map user input to the company dataset through logical "IF-THEN" rules. The research results demonstrate a chatbot accuracy rate of 90%, as measured through black box testing, despite limitations in handling input outside the trained dataset. The chatbot is designed with hybrid navigation, a simple interface, and cross-platform device compatibility. This research contributes to the development of chatbot based information systems that are widely accessible to customers, thereby enhancing user experience and improving operational efficiency for the company.